Формування нокаутуючого удару курсантів ВВНЗ інституцій сектору безпеки і оборони України - Хацаюк, О. В.; Khatsaiuk, O. V.; Гіренко, С. П.; Hirenko, S. P.; Волянський, В. Г.; Volianskyi, V. H.; Белошенко, Ю. К.; Beloshenko, Yu. K.; Гришко, А. В.; Hryshko, A. V.; Мердов, С. П.; Merdov, S. P.; et al. (Науковий часопис Українського державного університету імені Михайла Драгоманова. Серія 15: Науково-педагогічні проблеми фізичної культури (фізична культура і спорт). - 2024. - Вип. 7(180). - С. 194-201, 2024)
Відповідно до результатів аналізу науково-методичної та довідкової літератури, а також спеціалізованих Інтернет-ресурсів, членами науково-дослідної групи встановлено, що теоретичних (емпіричних) досліджень, які комплексно розкривають особливості формування індивідуальної техніки застосування заходів фізичного впливу (сили) військовослужбовцями інституцій сектору безпеки і оборони України зустрічаються рідко. В процесі теоретичного дослідження були використані наступні методи: аксіоматичні, ідеалізації, інструментальні, історичні і логічні, сходження від конкретного, формалізації, тощо. Крім цього, членами науководослідної групи використано особистий досвід організації системи спеціальної фізичної підготовки військовослужбовців (правоохоронців) інституцій сектору безпеки і оборони України. В результаті теоретичного дослідження членами науково-дослідної групи розроблено експериментальну програму формування нокаутуючого удару курсантів вищих військових навчальних закладів інституцій сектору безпеки і оборони України. Перспективи подальших досліджень у обраному напрямі наукової розвідки передбачають проведення апробації запропонованої нами програми на прикладі курсантів вищих військових навчальних закладів (закладів вищої освіти зі специфічними умовами навчання) інституцій сектору безпеки і оборони України.

During practical training, servicemen of different categories (age groups) learn and improve the technique of conducting Hand-to-Hand combat with an opponent (opponents) in various variable conditions, which involves striking blows with hands and feet, therefore the formation of a knockout blow by Cadets of Higher Military Educational Institutions (servicemen of various categories) Institutions of the Security and Defense Sector of Ukraine in today's realities is an important practical task. According to the Results of the analysis of Scientific and Methodological and reference literature, as well as Specialized Internet resources, the members of the Scientific Research group found that theoretical (empirical) studies that comprehensively reveal the peculiarities of the formation of individual techniques for the application of Measures of Physical Influence (Force) by Military personnel of Institutions of the Security Sector and Defenses of Ukraine are rare. In the process of Theoretical Research, the following Methods were used: axiomatic, idealization, instrumental, historical and logical, descent from concrete, formalization, etc. In addition, the Members of the Research group used their personal Experience of organizing a System of Special Physical training for Military Personnel (Law enforcement Officers) of Institutions of the Security and Defense Sector of Ukraine. As a Result of a theoretical study, the Members of the Research group developed a Program of forming a knockout blow for Cadets of Higher Military Educational Institutions of Institutions of the Security and Defense Sector of Ukraine. Prospects for Further Research in the chosen direction of Scientific Intelligence include testing the Experimental Methodology proposed by us on the example of Cadets of Higher Military Educational Institutions (Higher Education Institutions with Specific learning conditions) of Institutions of the Security and Defense Sector of Ukraine.

Разработана экспериментальная программа формирования нокаутирующего удара курсантов высших военных учебных заведений институтов СБОУ (на примере соискателей высшего образования Киевского института Национальной гвардии Украины).
The formation of a knockout blow by cadets of the Higher Military Educational Institutions of the Institutions of the Security and Defense Sector of Ukraine
Keywords: вибухова сила; заходи фізичного впливу; індивідуалізація; майбутні офіцери; методика; програма; професійна освіта; сила; спеціальна фізична підготовка; ударна техніка; швидкісно-силові якості; explosive force; measures of physical impact; individualization; future officers; methodology; program; professional education; strength; special physical training; impact technique; speed-power qualities; взрывная сила; меры физического воздействия; индивидуализация; будущие офицеры; программа; профессиональное образование; специальная физическая подготовка; ударная техника; скоростно-силовые качества